Corporate social responsibility, sustainability, and ethical public relations : strengthening synergies with human resources - Pompper, Donnalyn, 1960- (Emerald Publishing Limited, 2017)
Nowhere is the study of workplace ethics more relevant today than in the context of empowering organizations to meet their goals in corporate social responsibility and sustainability (CSR/S). Aimed at helping organizations uphold their commitments to people and the planet as well as profit, these are core goals towards which both PR and HR departments now work. However one major stumbling block is the fact that while internal departments may regularly work closely when managing and communicating with employees, the communication flow tends to be top down. In order to create more socially responsible, sustainable, and ethical organizations, the communication flow must be more organic and bilateral. The question of how both teams could work together on a more even playing field has escaped scholarly inquiry for years. Corporate Social Responsibility, Sustainability, & Ethical Public Relations: Strengthening Synergies with Human Resources examines ways to make CSR/S an integrated ingredient and ethical hallmark for an organization's culture. Here authors from around the globe use a variety of research methods to offer practical, empirical findings, exploring opportunities for employees to serve as a conduit for organizations' CSR/S goals. This book shows how HR-PR department cooperation can fulfil the role of organizational conscience, helping for-profits and non-profits to navigate toward greater CSR/S.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Social responsibility of business; Business communication